Tissue Transglutaminase Expression and Activity in Normal and Glaucomatous Human Trabecular Meshwork Cells and Tissues - Tovar-Vidales, Tara (2008)
PURPOSE: Glaucoma is a leading cause of irreversible visual impairment and blindness in the world. A major risk factor for glaucoma is elevated intraocular pressure due to increased resistance of aqueous humor outflow through the trabecular meshwork (TM). In the glaucomatous TM, there is increased accumulation of extracellular matrix (ECM) material due to a disruption of the normal balance between ECM deposition and degradation. Tissue transglutaminase (TGM2) belongs to a family of calcium-dependent enzymes that catalyze the posttranslational modification of the ECM by cross-linking proteins, thus making these proteins resistant to enzymatic and physical degradation. It is possible that the increase in ECM proteins in the glaucomatous TM is due to increased cross-linking activity of TGM2. The purpose of this study was to determine whether there are differences in expression and activity of TGM2 between normal and glaucoma TM cells and tissues. METHODS: Normal (n = 3 NTM) and glaucomatous (n = 3 GTM) human TM cell lines were grown until confluent. Western immunoblot analysis of cell lysates was used to compare TGM2 protein levels in NTM and GTM cells. TGM2 enzyme activity between NTM and GTM cells was studied by using a biotin cadaverine assay. In addition, immunohistochemistry of three normal and three glaucomatous TM tissues was used to evaluate the in vivo expression of TGM2, fibronectin (FN) and ε-(γ-glutamyl) lysine (GGEL) proteins. RESULTS: Western blot analysis and immunohistochemistry demonstrated the presence of TGM2 protein in both NTM and GTM cells. There was an increase in TGM2 protein in GTM cells compared with NTM cells, and GTM cells also had increased in TGM2 enzyme activity compared with NTM cells. Immunohistochemical results demonstrated increased expression of TGM2 and FN in GTM tissues. FN and GGEL proteins were colocalized in GTM tissues, indicating significant cross-linking of FN by TGM2. CONCLUSIONS: This study demonstrated that both NTM and GTM cells express TGM2. In addition, TGM2 protein levels and enzyme activities were elevated in GTM cells. There was also an increase in colocalization of FN and GGEL protein in GTM tissues. These results indicate that TGM2 may play an important role in the pathogenesis of glaucoma by cross-linking ECM proteins such as FN and thus making the ECM more resistant to degradation.